Sufetula culshawi sp. nov. (Lepidoptera, Crambidae, Lathrotelinae): a previously unrecognised species affecting cultivated palms - Mark R. Young; Peter R. Hall; Nigel G.J. Richards; David C. Lees (Nota Lepidopterologica)
A new species of the pantropical genus Sufetula Walker, 1859 (Crambidae: Lathrotelinae) is described. A male specimen was found by Martin Culshaw as an accidental import in Stirlingshire, Scotland, whilst a female specimen was later found in the Natural History Museum collections, which had been reared in southernmost Kyushu, at Ibusuki, Japan. These specimens do not match externally the 31 currently accepted described species in the genus. We obtained a full 658 bp DNA barcode from both specimens (together with all of COI from the Japanese exemplar) that confirmed their conspecificity but showing at least 7.49% p-distance from any presently existing cluster. Phylogenetic analysis, including 14 other exemplars with DNA barcodes from BOLD/GenBank, failed to place the new taxon with any existing lathroteline species group. The Japanese specimen was reared from the roots of an Areca Palm Chrysalidocarpus lutescens Wendland in 1987, whilst the specimen imported to Scotland may have emerged from the same species. This information suggests that the new species is a previously unrecognised coloniser of horticulturally imported palms. Currently we cannot rule out the hypothesis that the species is native to habitats containing palms in the southern Japanese islands, and further specimens should be searched for in collections and in the wild. However, INaturalist images externally diagnostic for the species suggest it is widespread in South East Asia.